Power, Performance, and Area-efficient Designs at Lower Nodes: Saving Billions in Semiconductor Manufacturing - Manoj Murali (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The semiconductor industry faces increasing challenges as technology nodes advance below 7nm, with optimization of power consumption, performance, and silicon area (PPA) becoming critical for financial success. This article explores the journey from Register-Transfer Level code to manufactured silicon, detailing optimization opportunities at each design stage. From RTL design and functional verification through logic synthesis, physical design, and timing closure, each phase offers significant potential for efficiency improvements. The economic implications of these optimizations span across market segments, including mobile devices, data centers, consumer electronics, enterprise systems, and IoT applications. A case study demonstrates how seemingly modest die size reductions can translate to substantial manufacturing cost savings at scale. The article illustrates why leading semiconductor companies invest heavily in design optimization techniques despite time-to-market pressures, as excellence in PPA optimization has evolved from a technical discipline to a core business competency with a direct impact on corporate financial performance.